Physical activity interventions for glycaemic control in African adults – A systematic review and meta-analysis. Issue 12 (December 2022) - Rao, Chythra R.; Chandrasekaran, Baskaran; Ravishankar, N.; Rutebemberwa, Elizeus; Okello, David
Abstract: Background and aim: Growing evidence indicates that increasing physical activity may aid in regulating altered glycaemic control, thereby mitigating the risk of diabetes. However, the evidence summarising the efficacy of physical activity on glycaemic control among African adults remains unconsolidated. Our objective was to provide an amalgamated summary of the empirical evidence that explored the effectiveness of physical activity interventions on glycaemic control among African adults. Methods: A systematic search of six journal databases for the studies exploring the efficacy of physical activity on glycaemic control among African adults until March 21, 2022, was administered. Two independent reviewers screened the citations based on a priori set eligibility criteria. Data were analysed using inverse variance method and a summary of findings was synthesised using the Grading of Recommendations, Assessment, Development and Evaluations approach. Results: Of the 14, 624 citations retrieved, 26 articles with 1474 participants were included for final analysis. Most of the included trials had a high risk of bias (N = 20; 76.92%). Our review found a significant reduction in fasting blood glucose (FBG,  −2.18 [ 95% CI -3.18,  −1.18] mmol/L), insulin (−0.99 [-2.71, 0.74] μU/L), Glycosylated haemoglobin (HbA1C) (−0.53% [-0.88,  −0.19]), Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) (−0.74% [-1.10,  −0.38]) and insulin sensitivity (−0.90 μU/l/min [-1.75,  −0.06]) following physical activity interventions. The review reports low certainty of evidence across all outcome measures. Discussion and conclusion: Physical activity interventions were found to improve glycaemic control among African adults. However, the optimal physical activity dose for demonstrating meaningful benefits on glucose tolerance still remains unclear due to the limited number of primary studies available. Highlights: Differences in glycaemic risk exist among African adults compared to white counterparts. Limited available evidence indicates improvement in glycaemic control with physical activity interventions. Effects of physical activity on glucose tolerance and insulin sensitivity remain inconsistent.